2017
DOI: 10.1007/s10522-017-9678-8
|View full text |Cite
|
Sign up to set email alerts
|

Middle age enhances expression of innate immunity genes in a female mouse model of pulmonary fibrosis

Abstract: The lungs are highly sensitive to tissue fibrosis, with a clear age-related component. Among the possible triggers of pulmonary fibrosis are repeated inhalations of fine organic particles. How age affects this response, is still far from being fully understood. We examined the impact of middle-age on gene expression in pulmonary fibrosis, using the novel "inhalation challenge set" mouse model. Our results demonstrate that the response of female mice to exposure of Pantoea agglomerans extract primarily involves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Pathological changes observed in mice in response to chronic exposure to the antigen of P. agglomerans were similar to the clinical picture of HP, which was confirmed on the genome and proteome level as well as in the microscopic image of lung tissue and in the characteristics of the immune response. Furthermore, earlier studies by our team also revealed that depending on the time of exposure, successive stages of disease development can be obtained: acute with a strong inflammatory response (7–14 days of exposure) and chronic with significant signs of fibrosis (28 days of exposure) [ 47 , 48 , 49 , 50 , 51 ]. It should be emphasized that according to our best knowledge, the mentioned model is the only research model of HP that, under laboratory conditions, reproduces the environmental exposure to organic dust causing lung fibrosis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Pathological changes observed in mice in response to chronic exposure to the antigen of P. agglomerans were similar to the clinical picture of HP, which was confirmed on the genome and proteome level as well as in the microscopic image of lung tissue and in the characteristics of the immune response. Furthermore, earlier studies by our team also revealed that depending on the time of exposure, successive stages of disease development can be obtained: acute with a strong inflammatory response (7–14 days of exposure) and chronic with significant signs of fibrosis (28 days of exposure) [ 47 , 48 , 49 , 50 , 51 ]. It should be emphasized that according to our best knowledge, the mentioned model is the only research model of HP that, under laboratory conditions, reproduces the environmental exposure to organic dust causing lung fibrosis.…”
Section: Discussionmentioning
confidence: 95%
“…The current study fills this gap of knowledge, describing the cathelicidin impact on the expression of genes and proteins involved in EMT under developing lung fibrosis in the course of HP. The study was conducted in created and validated by our research group the murine model of HP, wherein pulmonary fibrosis was induced by an extract of Pantoea agglomerans administered daily for 28 days to fibrosis mice strain C57BL/6J [ 47 , 48 , 49 , 50 , 51 ]. Pathological changes observed in mice in response to chronic exposure to the antigen of P. agglomerans were similar to the clinical picture of HP, which was confirmed on the genome and proteome level as well as in the microscopic image of lung tissue and in the characteristics of the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the proof that the secretome of senescent fibroblasts is profibrotic appears of particular relevance [24]. The findings of abnormal shortening of telomeres, observed in a number of fHP patients [25,26], as well as the demonstrations that the response to inhalational antigens differs in young and in old mice or that fibrosing HP is mostly diagnosed in elder patients [27][28][29] might indeed suggest a relationship between cellular senescence and fibrosis. Further studies will be of help to deeply clarify whether and how senescent cells might contribute to progressive fibrosis in HP or to determine if the usage of senolytic drugs, clearing senescent cells, could attenuate lung injury and inhibit fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…A 2017 study shows that NK cell-mediated cytotoxicity is particularly up-regulated in the IPF mouse model. 63 A 2019 clinical trial shows that the percentage of NK cells in IPF patients' bronchoalveolar lavage is associated inversely with their forced vital capacity and diffused lung carbon monoxide, 8 and increased serum IFN-γ level is found to be associated with acute exacerbation of IPF patients. 64 Similarly, monocytes primed by type-I IFNs (IFN-α, IFN-β) are considered to be a driving factor of aberrant injury repair and fibrosis.…”
Section: Discussionmentioning
confidence: 99%